2007
DOI: 10.1007/978-3-540-75670-5_13
|View full text |Cite
|
Sign up to set email alerts
|

On the Notions of PRP-RKA, KR and KR-RKA for Block Ciphers

Abstract: Abstract. Security of commonly used block ciphers is commonly measured in terms of their resistance to known attacks. While the provable security approach to block ciphers dates back to the first CRYPTO conference (1981), analysis of modern block cipher proposals typically do not benefit fully from this, except for a few cases. This paper considers the security of recently proposed PRP-RKA secure block ciphers and discusses how they relate to existing types of attacks on block ciphers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…(8) are discretized using Alternating Direction Implicit (ADI) scheme and the resulting system of finite difference equations are solved using 'Thomas Algorithm'. The computer code validation and grid independence test are explained in detail in [29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…(8) are discretized using Alternating Direction Implicit (ADI) scheme and the resulting system of finite difference equations are solved using 'Thomas Algorithm'. The computer code validation and grid independence test are explained in detail in [29][30][31].…”
Section: Methodsmentioning
confidence: 99%
“…A preliminary extended abstract version of this section appeared in [35]. In [16], it was shown that the advantage Adv kr E (A) of any KR adversary A mounting a generic attack depends on the number t of verifications made to the block cipher E (i.e., evaluations of the form E Ki (M i ) for any text M i and any key K i of the adversary's choice), and on the key bit-length k. More specifically, it was shown that:…”
Section: Security Of Three Prp-rka Ciphers Against Key Recoverymentioning
confidence: 99%